Analisis Profil Kebiasaan Belajar Matematika sebagai Cermin Pendidikan Karakter di Sekolah - Neza Juspika; sujiani; Aura Anisa; Siti Sarah (Universitas Mercu Buana Yogyakarta, 2025)
This study aims to analyze students’ mathematics learning habits as a reflection of the implementation of character education in schools. A descriptive quantitative method was employed using a questionnaire instrument to measure several character-related aspects, including responsibility, discipline, honesty, and initiative in learning mathematics. The results show that the responsibility aspect received the highest score (4.21), indicating that students generally complete their tasks independently and on time. Discipline (3.88) and honesty (3.67) were also rated as good, although some students still exhibited inconsistent learning behaviors. The lowest score was found in the initiative to ask questions or understand material (3.45), suggesting the need to strengthen work ethic and self-confidence in learning, especially when dealing with difficult mathematical concepts. These findings support previous studies that emphasize the importance of cultivating character values through daily learning practices. Overall, the mathematics learning habits profile can serve as a strong indicator for assessing the effectiveness of character education, with teachers playing a central role through modeling, habituation, and reflective instruction.